Perancangan dan Implementasi Sistem Sewa Mobil untuk Kendaraan Operasional - Putri, Elfara Nadiva; Harahap, Adriansyah Putra (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2024)
PT Indonesia Comnets Plus (ICON+) Regional West Java SBU requires improved efficiency in managing operational vehicle rentals, which was previously done manually. This study aims to design and implement a web-based vehicle rental system using the Laravel framework to simplify the rental process and data management. The system is designed based on 107 functional requirements and 15 non-functional requirements, developed using the agile scrum approach, which includes five stages: 1) sprint planning, 2) system development, 3) testing, 4) sprint review, and 5) deployment. The testing was conducted using Blackbox Testing and User Acceptance Testing (UAT). The results of the study show that the implemented system successfully enhances operational efficiency, minimizes the risk of errors, and facilitates monitoring vehicle usage through an integrated dashboard. The UAT results indicate that the system falls under the "Strongly Agree" category, with functionality at 86.8%, reliability at 88.5%, usability at 90%, and efficiency at 93.6%, with an overall rating of 89.41%. These results suggest that the system meets the expected quality characteristics and effectively supports operational processes. Keywords: efficiency vehicle rental system, agile scrum, operational efficiency, Laravel framework, digitalization of vehicle rentals